2011
DOI: 10.1111/j.1439-0396.2011.01239.x
|View full text |Cite
|
Sign up to set email alerts
|

Egg yolk fatty acid profile of avian species – influence on human nutrition

Abstract: SummaryLipids are an important nutritional component of the avian egg. A review of the literature was completed to determine the fatty acid compositions in egg yolk from some avian species.Additionally, the nutritional influence of lipid and lipoproteins content in the plasma of male participants during 30-d feeding was discussed. The ostrich eggs had the highest unsaturated fatty acid and the lowest cholesterol content vs. other avian species. Ostrich had a higher proportion of 18:3n-3 (p<0.01) vs. other spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 79 publications
4
17
0
1
Order By: Relevance
“…The yolk was rolled on a damp paper towel to dry the remaining albumen residue. The chalaziferous were carefully removed with forceps before the yolk was weighed (Golzar Adabi et al, 2013).…”
Section: Methodsmentioning
confidence: 99%
“…The yolk was rolled on a damp paper towel to dry the remaining albumen residue. The chalaziferous were carefully removed with forceps before the yolk was weighed (Golzar Adabi et al, 2013).…”
Section: Methodsmentioning
confidence: 99%
“…Egg yolks contain a higher ratio (30:1) of linoleic acid (18:2 n‐6) to α‐linolenic acid (18:3 n‐3) than is desired for efficient conversion of α‐linolenic acid to DHA, with some variability across eggs from different avian species . Several studies in which eggs were “field” fortified through the use of n‐3 supplements in hen feed and other technologies showed increased DHA content, which was associated with positive health and nutrition outcomes .…”
Section: Egg Nutrient Compositionmentioning
confidence: 99%
“…Eggs are a good source of lutein and zeaxanthin, carotenoids that protect against lipoprotein oxidation . Other vitamins critical to the health of vulnerable populations, such as E, D, B 12 , and folate, are also found in eggs . One study examining the adequacy of micronutrient intakes in rural Bangladesh found eggs contributed 40.8% of vitamin B 12 intake among young children and 29.4% among women …”
Section: Egg Nutrient Compositionmentioning
confidence: 99%
“…26, 27 To assess how lipophilic compounds influence properties of whole EY, we performed hexane extraction procedure on the EY (Fig. 1A) and characterized the composition of the non-polar (EY-NP), and polar (EY-P) fractions.…”
Section: Resultsmentioning
confidence: 99%